A Systematic Review of the Recent Quality of Life Studies in Adult Extremity Sarcoma Survivors. (23rd August 2012) - Tang, Melissa H.; Pan, Donald J. W.; Castle, David J.; Choong, Peter F. M.
Abstract : Background . Extremity sarcoma represents a heterogeneous group of rare cancers that carries a relatively high morbidity with regards to physical function. Quality of Life (QoL) as an outcome is an important consideration in this cohort. We aimed to identify the correlates of QoL in extremity sarcoma cohorts. Methods . A systematic review of the literature on extremity sarcoma in adults from five databases over the last ten years was undertaken. Results . Twelve articles were chosen and assessed for quality. Physical and social function of extremity sarcoma survivors is below that of the general population. Overall QoL scores of these patients are comparable to those of the general population. Studies that used more recently treated cohorts found that patients who had limb sparing surgery displayed superior functional outcomes over those that underwent amputations. Pain and perceiving that the cancer negatively influenced opportunities was associated with poor outcomes. Conclusion . The available literature regarding QoL in extremity sarcoma patients is heterogeneous in terms of aims and assessment tools. Results need to be interpreted in light of the improved management of extremity sarcoma in more recent patient cohorts.